Unveiling Barriers to Telehealth Adoption among Employees with Metabolic Syndrome: Innovation Resistance Theory Perspective - Rahardi, Rafi Amani Muflih; Isoagi, Chieviog Igiobye; Ningsih, Muflihuun Retno (TIN: Terapan Informatika Nusantara, 2025)
This study explores the key barriers hindering the adoption of telehealth services among employees diagnosed with Metabolic Syndrome (MetS), using the Innovation Resistance Theory (IRT) framework. The focus on office employees is justified, as this group is highly susceptible to MetS due to sedentary work routines that elevate cardiometabolic risks, making telehealth a potentially valuable tool for continuous monitoring and disease management. A quantitative approach was employed with data collected from 400 office-based employees with MetS in Indonesia via an online survey. Constructs related to usage, value, risk, tradition, and image barriers were measured and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that all five barriers significantly and negatively influence the intention to use telehealth, with usage barrier (β = −0.274; p = 0.001) and image barrier (β = −0.196; p = 0.000) exerting the strongest effects. The model demonstrates strong explanatory power, with R² values of 0.600 for intention to use and 0.515 for actual usage. Furthermore, intention to use was found to significantly predict actual usage and mediate the effects of resistance barriers on adoption behavior. These findings highlight the need to enhance system usability, increase perceived value, and build a credible telehealth image. This research contributes to telehealth literature by validating IRT in a chronic disease context and offering strategic insights for service developers, healthcare policymakers, and digital health marketers aiming to reduce resistance and boost adoption.